The Influence of the Giving Question and Getting Answer Learning Model on the Motivation and Social Studies Learning Outcomes of Class V Students - Asmawati A; Kaharuddin Kaharuddin; Jamaluddin Jamaluddin (Edumaspul: Jurnal Pendidikan, 2024)
The aim of this research is to determine the influence of the Teaching Learning Model of Giving Qualifications and Learning Answers on the motivation and social studies learning outcomes of class V students at SD Inprels Lambelngi, Pallangga District, Gowa Regency. This type of research is quantitative using an experimental approach. The research design used is Nonequivalent Control Group Design. The population in this study was 40 students. Data collection techniques in this research are questionnaires, tests, observation and documentation. The data analysis techniques used are descriptive data analysis and inferential statistical analysis. The hypothesis test used is the Anova and Manova tests. The research results obtained were; 1) Student learning motivation is 0.000 < 0.05, which means H1 is accepted and H0 is rejected, namely there is an influence of the Giving Question and Getting Answer Learning Model on the learning motivation of class V students. 2) Student learning outcomes are 0.000 < 0.05, which means H1 is accepted and H0 is rejected, namely there is an influence of the Giving Question and Getting Answer Learning Model on the learning outcomes of class V students and 3) The significance value of students' motivation and social studies learning outcomes is smaller than 0.05 which means H1 is accepted and H0 is rejected, namely there is an influence of the Model Giving Qulelstion and Geltting Answelr learning on the motivation and learning outcomes of social studies for fifth grade students at Inprels Lambelngi Elementary School, Pallangga District, Gowa Regency